Classical capillary turbulence on the surface of quantum liquid He-II - Abdurakhimov, L.V.; Brazhnikov, M.Yu.; Remizov, I.A.; Levchenko, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Superfluid helium-4 is a unique liquid for experimental study of capillary wave turbulence due to its very low viscosity. We have studied the influence of amplitude and spectral characteristics of the excitation force on the behavior of the turbulent cascade of capillary waves in the cylindrical cell of diameter 30 mm. We have found that the experimental results can be explained within the framework of the wave turbulence theory (WTT) when the amplitude of pumping is relatively high. However, a very interesting phenomenon was observed at moderate amplitudes of harmonic surface excitation. It was detected the deviation of the turbulent spectrum from the power law function predicted by WTT at high frequencies — local maximum — that can be interpreted as wave energy accumulation. Our estimations show that the special case of wave turbulence is realized in our measurements, namely, discrete turbulence which is characterized by the strong influence of discreteness of cell resonant frequencies on the mechanism of the nonlinear interaction.